Satellite Data Reveal Cropland Losses in South-Eastern Ukraine Under Military Conflict - Skakun, Sergii; Justice, Christopher O.; Kussul, Nataliia; Shelestov, Andrii; Lavreniuk, Mykola (Frontiers in Earth Science, 2019)
While people are aware that there is a continuing conflict in Ukraine, there is little understanding of its impact. The military conflict in South-Eastern Ukraine has been on-going since 2014, with a major socio-economic impact on the Donetsk and Luhansk regions. In this study, we quantify land cover land use changes in those regions related to cropland changes. Cropland areas account for almost 50% of the Donetsk and Luhansk regions, and with the declining industry between 2014–2017, the role of agriculture to the regional economy has increased. We use freely available satellite data and machine learning methods to map cropland extent in 2013 and 2018 and derive corresponding changes in cropland areas. We use a multi-layer perceptron (MLP) to classify multi-temporal Landsat-7, Landsat-8 and Sentinel-2 images into cropland and non-cropland areas, and a sampling-based approach to estimate the areas of cropland change. We found that net cropland losses were not uniform across the regions, and were more substantial in the areas not under control of the Ukrainian Government (22% of net cropland area loss compared to cropland areas in 2013) and within a buffer zone along the conflict border line (46%), where combat activities occur. These results highlight the impact of the conflict on agriculture and the utility of spatially explicit information acquired from Earth observation satellites, especially for areas, where collecting ground-based data is impractical.